Kesiapan Kerja Mahasiswa di Era Digital: Peran Literasi Digital, Soft Skill, dan Motivasi - Vanissa Fatimatul Zahra; Danny Ramdani (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the influence of digital literacy, soft skills, and motivation on the readiness to enter the workforce of 2022 students at Singaperbangsa University, Karawang. The study used a quantitative approach with a verification method. The study population was 4,215 students, while a sample of 366 respondents was determined using the Taro Yamane formula with a simple random sampling technique. Data collection was carried out through distributing questionnaires and analyzed using multiple linear regression with the help of IBM SPSS Statistics 25. The results showed that digital literacy had a positive and significant effect on job readiness with a calculated t value of 7.066 and a significance of 0.000. Soft skills also had a positive and significant effect on job readiness with a calculated t value of 6.581 and a significance of 0.000. Furthermore, motivation had a positive and significant effect on job readiness with a calculated t value of 8.944 and a significance of 0.000. Simultaneously, digital literacy, soft skills, and motivation have a positive and significant effect on students' work readiness with a calculated F value of 443.578 and a significance level of 0.000. This finding indicates that improving digital literacy, soft skills, and motivation in an integrated manner can improve students' readiness to face the demands of an increasingly competitive and digitalized world of work